2004
DOI: 10.3201/eid1004.030506
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Gene Delivery in Animal Feeds

Abstract: Avoparcin, a glycopeptide antimicrobial agent related to vancomycin, has been used extensively as a growth promoter in animal feeds for more than 2 decades, and evidence has shown that such use contributed to the development of vancomycin-resistant enterococci. A cluster that includes three genes, vanH, vanA, and vanX, is required for high-level resistance to glycopeptides. In the vancomycin producer Amycolatopsis orientalis C329.2, homologs of these genes are present, suggesting an origin for the cluster. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Recently, Lu and coworkers (21) found substantial bacterial DNA contamination, including nucleotide sequences consisting of the three genes vanH, vanA, and vanX that are required for high-level resistance to the glycopeptides in animal feedgrade avoparcin. They suggested that the prolonged use of avoparcin in agriculture may have led to the uptake of glycopeptide resistance genes by commensal bacteria in animals, which were subsequently transferred to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lu and coworkers (21) found substantial bacterial DNA contamination, including nucleotide sequences consisting of the three genes vanH, vanA, and vanX that are required for high-level resistance to the glycopeptides in animal feedgrade avoparcin. They suggested that the prolonged use of avoparcin in agriculture may have led to the uptake of glycopeptide resistance genes by commensal bacteria in animals, which were subsequently transferred to humans.…”
Section: Discussionmentioning
confidence: 99%
“…A main concern is a hypothesized horizontal gene transfer to clinically relevant bacteria (22,24), although such a link has never been documented (30). Antibiotic formulations used in animal feeds have been suggested as a potential delivery vehicle for resistance genes (1,8,21), since low-grade formulations have been shown to be contaminated with the resistance genes of producer organism used to prepare formulations (15,28,29). Streptomycin formulations used in plant agriculture are produced using Streptomyces griseus subsp.…”
mentioning
confidence: 99%
“…In these, there is a complex web of much more important sources and factors that affect the stability, recycling, and horizontal transfer of (at least some) ARMGs (Martinez 2009). Occasional or mass-scale delivery of ARMGs, including the aadA gene (Binh et al 2009), into the ecosystem is very well characterized: DNA-contaminated veterinary antibiotics (Lu et al 2004), resistant microbial biocontrol agents (Zhang et al 2006), livestock manure (Heuer et al 2011;Marti et al 2013a;Udikovic-Kolic et al 2014), and waste water or even drinking (including chlorinated) water (Xi et al 2009;Marti et al 2013b;Shi et al 2013) are all identified and proven components of this antibiotic resistance cycle. Through the same channels, also antibiotics are efficiently distributed, which provides an increased pressure for the selection of further antibiotic-resistant microbes.…”
Section: Public Concerns Associated With Transplastomic Plantsmentioning
confidence: 99%